Assessing L2 listening : moving towards authenticity - Ockey, Gary J.; Wagner, Elvis (Language learning and language teaching, 2018)
"This book is relevant for language testers, listening researchers, and oral proficiency teachers, in that it explores four broad themes related to the assessment of L2 listening ability: the use of authentic, real-world spoken texts; the effects of different speech varieties of listening inputs; the use of audio-visual texts; and assessing listening as part of an interactive speaking/listening construct. Each theme is introduced with a review of the relevant literature, and then is examined through either two or three empirical studies. The notion of authenticity underlies each of these four themes. By creating more authentic test tasks that are similar to real world language tasks, test developers can create listening assessments that not only more effectively assess test takers' communicative competence, but can also have a positive washback effect on educational systems"--